GEOMETRIC PROBLEMS OF CONSTRUCTION - DETERMINANT FACTOR IN THE INTELLECTUAL EDUCATION OF PUPILS AND STUDENTS - CALMUȚCHI, Laurențiu (Acta et Commentationes, Sciences of Education, 2019)
This article investigates the methodology of solving constructive problems by applying different methods to solve these problems. Particular attention is paid to researching problem solutions.